2018
DOI: 10.1007/s00167-018-5103-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic knee joint alignment and orientation can be restored by the minimally invasive double level osteotomy for osteoarthritic knees with severe varus deformity

Abstract: Retrospective case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 38 publications
(62 reference statements)
4
107
0
5
Order By: Relevance
“…2). Therefore, it cannot be concluded from our data that overcorrections must be avoided and double level osteotomies should be performed, but other clinical and experimental data indicate this very strongly [7,9,10,23,24]. The maximum overcorrection that can be tolerated in femoral and tibial osteotomies should be examined more closely in further studies.…”
Section: Mechanical Axis and Joint Anglesmentioning
confidence: 79%
“…2). Therefore, it cannot be concluded from our data that overcorrections must be avoided and double level osteotomies should be performed, but other clinical and experimental data indicate this very strongly [7,9,10,23,24]. The maximum overcorrection that can be tolerated in femoral and tibial osteotomies should be examined more closely in further studies.…”
Section: Mechanical Axis and Joint Anglesmentioning
confidence: 79%
“…• [36]. With regard to the mMPTA, two different simulations were performed: one simulation with a postoperative upper limit of 90° (anatomic correction) and another simulation with a postoperative upper limit of 95° (overcorrection).…”
Section: Deformity Analysismentioning
confidence: 99%
“…DLO was indicated for knees exhibiting deformity in both the femur and tibia, and for patients with high activity level who wished to retain the level of activity after surgery. 13 Preoperative surgical planning was performed using digital planning software (mediCADR, Hectect, Germany) on a standing full-length anteroposterior radiograph. 15 The indication for DLO was severe varus malalignment and medial compartment osteoarthritis.…”
Section: Methodsmentioning
confidence: 99%
“…There have been several studies reporting favorable surgical outcomes of DLO. 12 , 13 , 14 Those reports have shown that DLO enables restoration of normal limb alignment without causing non-physiologic joint line inclination as observed in isolated MOWHTO knees; however, most of the previous relevant studies dealt with correction of the femoro-tibial alignment, and associated changes in the patellofemoral joint have not been addressed. Although there have been studies investigating the changes in the patellar position and orientation following MOWHTO, there is lack of information regarding the effects of DLO on patellar height or patellofemoral alignment.…”
Section: Introductionmentioning
confidence: 99%